Enhancing the Overall Heat Transfer Coefficient through Tube Rotation of a Heat Exchanger: An Analytical Approach - Subrahmanyam, Nistala V.; Muthuraman, Jayadeekshitha; Raj, Karthik; Nallamothu, Mahesh; Pal, Dipankar (Recent Innovations in Chemical Engineering, 2022)
Background: Flow in an annulus between two concentric cylinders or pipes is very often observed, ranging its applications in many streams, namely, in steam generators, condensers, petroleum science and engineering, and various flow devices in chemical processing industries. The objective is to prove or understand the essence of parameters like heat transfer coefficient, mass transfer coefficient, etc., depending on such flow regimes. One such piece of equipment found in industry is a heat exchanger, where heat transfer occurs from one medium to another. Objective: The present study majorly discusses increasing the heat transfer coefficient in the case of shell and tube heat exchangers with rotation of tubes and is restricted to a single tube inside a shell. Methods: The methodology section can be broadly divided into two categories. First, the theoretical solution (obtained under certain assumptions) of the flow between two concentric cylinders, which includes both the rotation case and no rotation case. And second, ANSYS Fluent simulations have been presented at a steady state for both cases. All required conditions, dimensions of the chosen geometry, and assumptions have been clearly mentioned before getting into the discussion or along the way. Moreover, this study is a kind of comparative study between the conventional method of operating and rotation of tubes inside the shell and tube heat exchangers. Results: The results were positive from both the ways – theoretical and ANSYS, that there was a certain increase in the heat transfer coefficient. The overall heat transfer coefficient increased at varying flow rates (0.25 kg/s, 0.5 kg/s, and 1 kg/s) at different speeds of rotation (100 RPM, 200 RPM, and 300 RPM). Conclusion: One of the most common equipment in industries is heat exchanger. Parameters like heat transfer coefficient can be increased by rotating tube(s) of heat exchanger. This was presented using two approaches- analytical and simulation techniques. On varying RPM from 0 to 300, heat transfer coefficient increased by 69.1% for 1 kg/s, 124.7% for 0.5 kg/s, and 172.3% for 0.25 kg/s.
Keywords: ANSYS fluent